2015
DOI: 10.1111/tpj.13019
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and phosphoproteomic analyses reveal extensive phosphorylation of regulatory proteins in developing rice anthers

Abstract: SUMMARYAnther development, particularly around the time of meiosis, is extremely crucial for plant sexual reproduction. Meanwhile, cell-to-cell communication between somatic (especial tapetum) cells and meiocytes are important for both somatic anther development and meiosis. To investigate possible molecular mechanisms modulating protein activities during anther development, we applied high-resolution mass spectrometry-based proteomic and phosphoproteomic analyses for developing rice (Oryza sativa) anthers aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 101 publications
4
71
0
Order By: Relevance
“…Consistently, most of those proteins are also involved in distinct metabolic pathways related to tapetum function, for instance callose and pollen wall development. A comparison of our previously reported RAM phosphoproteome (Ye et al ., ) and the lysine acetylome here revealed that proteins encoding transcription factors are preferentially modified by phosphorylation, while those functioning as enzymes are more likely to be acetylated (Figure ). In particular, among known functional proteins involved in tapetum and pollen development, we found that eight were acetylated.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations
“…Consistently, most of those proteins are also involved in distinct metabolic pathways related to tapetum function, for instance callose and pollen wall development. A comparison of our previously reported RAM phosphoproteome (Ye et al ., ) and the lysine acetylome here revealed that proteins encoding transcription factors are preferentially modified by phosphorylation, while those functioning as enzymes are more likely to be acetylated (Figure ). In particular, among known functional proteins involved in tapetum and pollen development, we found that eight were acetylated.…”
Section: Resultsmentioning
confidence: 87%
“…To obtain clues about the subcellular localization of the KAC proteins in RAMs we performed enrichment of Gene Ontology (GO) term annotations for these proteins. The results showed that the largest proportion was assigned to cytoplasm, followed by membrane and nucleus (Figure a), similar to the pattern in the RAM phosphoproteome in our previous report (Ye et al ., ). In particular, 12.3%, 10.2%, 2.7% and 1.5% of the KAC proteins are located in the chloroplast, mitochondrion, endoplasmic reticulum (ER) and chromosome, respectively (Figure a).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Apart from this, the other possible reason behind biphasic protein accumulation of bHLH142 may lie in the enhancement of its protein stability. In the recent report, proteomic and phospho-proteomic analysis of rice meiotic anthers showed presence of bHLH142 protein in phospho-proteome43. Detection of bHLH142 protein in anther phospho-proteome suggested its post-translational level regulation that may change its stability.…”
Section: Discussionmentioning
confidence: 98%